THE EFFECT OF E-FILING POLICY, TAX SANCTIONS, AND TAXPAYER AWARENESS TOWARD TAXPAYER COMPLIANCE IN THE COVID-19 PANDEMIC - Narendra Eky Rezia Nuryanto; Lita Kusumasari (Jurnal Akuntansi Dan Manajemen, 2022)
The research purpose is to examine the effect of E-Filing policies, tax sanctions, and taxpayer awareness on taxpayer compliance during the covid-19 pandemic. This is quantitative research. The research used primary data obtained through a survey method with a questionnaire. The sampling method is convenience sampling collected from 120 taxpayers in Yogyakarta. The analysis is descriptive statistical, classic assumption test, and multiple linear regression. The data analysis technique of this research uses SPSS version 21. The results show that the E-Filing policy, tax sanctions, and taxpayer awareness have positive effects on taxpayer compliance during the covid-19 pandemic. The government can improve taxpayer compliance by managing and improving the E-Filing policies, carrying out routine supervision of taxpayer compliance, and increasing socialization about the importance of taxes for state development.